Formulation of ciprofloxacin-loaded oral self-emulsifying drug delivery system to improve the pharmacokinetics and antibacterial activity - Asghar, Asghar Ali; Akhlaq, Muhammad; Jalil, Aamir; Azad, Abul Kalam; Asghar, Junaid; Adeel, Muhammad; Albadrani, Ghadeer M.; Al-Doaiss, Amin A.; Kamel, Mohamed; Altyar, Ahmed E.; Abdel-Daim, Mohamed M. (Frontiers in Pharmacology, 2022)
The aim of current study was to increase aqueous solubility of ciprofloxacin (CPN) to improve oral bioavailability. This was done by formulating a stable formulation of Self-Emulsifying Drug Delivery System (SEDDS) by using various ratios of lipid/oil, surfactant, and co-surfactant. A Pseudo ternary phase diagram was designed to find an area of emulsification. Eight formulations (F1-CPN-F8-CPN), containing oleic acid oil, silicone oil, olive oil, castor oil, sunflower oil, myglol oil, polysorbate-80, poly-sorbate-20, PEO-200, PEO-400, PEO-600 and PG formulated. The resultant SEDDS were subjected to thermodynamic study, size, and surface charge studies to attain improved preparation. Improved composition of SEDDS F5-CPN containing 40% oil, 60% pol-ysorbate-80 and propylene glycol (Smix ratio 6: 1), were thermodynamically stable emulsion having droplet size 202.6 nm droplets, charge surface -13.9 mV and 0.226 polydispersity index (PDI). Fourier Transform Infra-Red (FTIR) studies revealed that optimized formulation and drug showed no interactions. Scanning Electron Microscope tests showed even surface and spherical shape of the droplets. It was observed that within 5hr., the concentration of released CPN from optimized formulations F5-CPN was 93%. F5-CPN also showed a higher antibacterial action against S. aurous as compared to free CPN. It shows that F5-CPN is a better formulation with good release and high antibacterial activity.